2007
DOI: 10.1111/j.1466-769x.2007.00332.x
|View full text |Cite
|
Sign up to set email alerts
|

Beleaguered by technology: care in technologically intense environments

Abstract: Modern technology has enabled the use of new forms of information in the care of critically ill patients. In intensive care units (ICUs), technology can simultaneously reduce the lived experience of illness and magnify the objective dimensions of patient care. The aim of this study, based upon two empirical studies, is to find from a philosophical point of view a more comprehensive understanding for the dominance of technology within intensive care. Along with caring for critically ill patients, technology is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 9 publications
0
50
0
2
Order By: Relevance
“…Researchers and theorists (Almerud, Alapack, Fridlund & Ekebergh, 2008;Barnard, 2002;Barnard & Sandelowski, 2001;Bennett, 2010Bennett, , 2011Bevan, 1998Bevan, , 2000McGibbon & Peter, 2008;Poland et al, 2005;Sandelowski, 2002;Tranter et al, 2009;Wynn, 2002;Zitzelsberger, 2004) have called for more research to investigate the nature and effects of technologies in and on specific places of care. Some studies explored nurses' views (Bull & FitzGerald, 2006;Marck, 2000;McGibbon & Peter, 2008;Tranter et al, 2009) and Allen et al (2011) andNagle (1998) identified the need to investigate similarities and differences between care recipients' and providers' perspectives of technologies and their settings.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers and theorists (Almerud, Alapack, Fridlund & Ekebergh, 2008;Barnard, 2002;Barnard & Sandelowski, 2001;Bennett, 2010Bennett, , 2011Bevan, 1998Bevan, , 2000McGibbon & Peter, 2008;Poland et al, 2005;Sandelowski, 2002;Tranter et al, 2009;Wynn, 2002;Zitzelsberger, 2004) have called for more research to investigate the nature and effects of technologies in and on specific places of care. Some studies explored nurses' views (Bull & FitzGerald, 2006;Marck, 2000;McGibbon & Peter, 2008;Tranter et al, 2009) and Allen et al (2011) andNagle (1998) identified the need to investigate similarities and differences between care recipients' and providers' perspectives of technologies and their settings.…”
Section: Discussionmentioning
confidence: 99%
“…Second, Guzetta [41] narrates the trajectory of her career, while explicating previous research studies influencing patient and nurse outcomes in acute care while weaving a body-mind-spirit tapestry. Lastly, Almerud and colleagues [19] use reflection and hyper-reflection to examine two previous phenomenological oriented studies to examine a philosophical point of view in order to understand the dominance of technology for intensive care nurses within an intensive care environment.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Reviewer one raised a point for discussion in that the Almerud [19] article was not based on original research because the method of reflection-hyperreflection are based on two previously published phenomenological studies. However, after much discussion it was determined that this paper would be included in the scoping review as grey literature because it met the inclusion criteria, purpose, and objective but also, because of its relevance and contribution to scoping review.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 2 more Smart Citations